Analisis Hukum Terhadap Perlindungan Data Pribadi (Studi Kasus @farida.nurhan dan @codebluuuu) - Sabina Tiffani; Faisal (Dinasti Review Publisher, 2024)
The development of information and communication technology in the digital era has resulted in increased use of personal data. Raising concerns about misuse of personal data such as identity dissemination or privacy violations. Therefore, legal regulations are needed to protect personal data. This research aims to find out and analyze the legal review of personal data protection, understand the scope of personal data, and examine the criminal liability of perpetrators who disseminate personal data. The method used in this research is the normative juridical method. The data source for this research uses secondary data obtained through library studies and literature research using various references from journals, ebooks, as well as laws or official documents issued by the government regarding the protection of personal data. Using the main legal basis, namely Law Number 27 of 2022 concerning Personal Data Protection, the results of this research show that perpetrators who distribute personal data can be punished. Personal data protection in Indonesia has a strong legal basis, strict law enforcement and public education need to be carried out to prevent the spread of personal data.